PENGARUH LIKUIDITAS, LEVERAGE DAN KOMISARIS INDEPENDEN TERHADAP AGRESIVITAS PAJAK PERUSAHAAN - Hidayat, Angga; Muliasari, Riri (SULTANIST: Jurnal Manajemen dan Keuangan, 2020)
This study aims to determine and provide empirical evidence regarding the Effect of Liquidity, Leverage and Independent Commissioners on Corporate Tax Aggressiveness in the Jakarta Islamic Index 2013-2017. The number of samples in the study were 10 companies obtained using the purposive sampling method based on predetermined criteria. The data used are secondary data in the form of audited annual financial statements in the period 2013 - 2017 taken from the sites www.idx.co.id and www.idx.co.id. Data analysis techniques used were descriptive statistics, assumptions test and multiple linear regression analysis tests. The results of the study were conducted based on the T test, liquidity using the quick ratio had no effect on tax aggressiveness, leverage it affected on tax aggressiveness and for independent commissioners too it affected tax aggressiveness. The results of the study are based on the F test, simultaneously liquidity and independent commissioners influence the aggressiveness of corporate taxes.